Tracheo-esophageal Puncture (TEP) for Voice Rehabilitation in Laryngectomised Patients Blom-singer® Vs Provox® Prosthesis : Our Experience - Ramalingam, WVBS (Med J Armed Forces India, 2007)
BACKGROUND: Stage III and IV cancers of larynx and hypopharynx often require total laryngectomy which leaves the patient with severe communication handicap. In such laryngectomised patients tracheo-esophageal puncture is the best way for voice rehabilitation using either Blom-Singer® prosthesis or Provox® indwelling valve. METHODS: A prospective comparative study of Blom-Singer® prosthesis and Provox® indwelling valves placed in Tracheo-esophageal Punctures (TEP) for voice rehabilitation following total laryngectomy was carried out at the Tata Memorial Hospital, Mumbai and Malignant Diseases Treatment Centre of Armed Forces, to assess their efficacy. This report comprises of our experience in 41 (39 males and two females) laryngtectomees who underwent TEP of which 15 patients were fitted with low pressure Blom-Singer® prostheses and 26 with Provox® indwelling prostheses. RESULTS: Prostheses related problems like granuloma formation, leakage, candidal growth over the valves and prosthetic decay were significantly less in the patients fitted with Provox® prosthesis. Dislodgement of prosthesis with closure of the tract or persistent fistula formation and creation of false passage, while reinsertion were problems encountered in the Blom-Singer group. After three months, speech assessment revealed a better quality of voice production and patient compliance in maintaining the prosthesis in the case of Provox® indwelling valve. CONCLUSION: In Indian scenario where illitracy amongst the patients hinders in maintainence of Blom-Singer® prosthesis, Provox® indwelling value is an appropriate choice for voice rehabilitation.